Can immigrants ever earn as much as native workers? - Kathryn H. Anderson (IZA World of Labor, 2019)
Immigrants contribute to the economic development of the host country, but they earn less at entry and it takes many years for them to achieve parity of income. For some immigrant groups, the wage gap never closes. There is a wide variation across countries in the entry wage gap and the speed of wage assimilation over time. Wage assimilation is affected by year of entry, immigrant skill, ethnicity, and gender. Policies that facilitate assimilation of immigrant workers provide support for education, language, and employment. Such policies can also reduce barriers to entry, encourage naturalization, and target selection of immigrants.
Keywords: J61; J68; J31; J38; 330; immigration; wages; inequality; assimilation; integration